Complex Formation of Myrosinase Isoenzymes in Oilseed Rape Seeds Are Dependent on the Presence of Myrosinase-Binding Proteins - Eriksson, Susanna (American Society of Plant Physiologists, 2002)
The enzyme myrosinase (EC 3.2.3.1) degrades the secondary compounds glucosinolates upon wounding and serves as a defense to generalist pests in Capparales. Certain myrosinases are present in complexes together with other proteins such as myrosinase-binding proteins (MBP) in extracts of oilseed rape (Brassica napus) seeds. Immunhistochemical analysis of wild-type seeds showed that MBPs were present in most cells but not in the myrosin cells, indicating that the complex formation observed in extracts is initiated upon tissue disruption. To study the role of MBP in complex formation and defense, oilseed rape antisense plants lacking the seed MBPs were produced. Western blotting and immunohistochemical staining confirmed depletion of MBP in the transgenic seeds. The exclusive expression of myrosinase in idioblasts (myrosin cells) of the seed was not affected by the down-regulation of MBP. Using size-exclusion chromatography, we have shown that myrosinases with subunit molecular masses of 62 to 70 kD were present as free dimers from the antisense seed extract, whereas in the wild type, they formed complexes. In accordance with this, MBPs are necessary for myrosinase complex formation of the 62- to 70-kD myrosinases. The product formed from sinalbin hydrolysis by myrosinase was the same whether MBP was present or not. The performance of a common beetle generalist (Tenebrio molitor) fed with seeds, herbivory by flea beetles (Phyllotreta undulata) on cotyledons, or growth rate of the Brassica fungal pathogens Alternaria brassicae or Lepthosphaeria maculans in the presence of seed extracts were not affected by the down-regulation of MBP, leaving the physiological function of this protein family open.